Analysis of Individuals from a Dengue-Endemic Region Helps Define the Footprint and Repertoire of Antibodies Targeting Dengue Virus 3 Type-Specific Epitopes - Daniela V. Andrade (American Society for Microbiology, 2017)
ABSTRACT The four dengue virus serotypes (DENV1 to 4) cause dengue, a major public health problem worldwide. Individuals exposed to primary DENV infections develop serotype-specific neutralizing antibodies, including strongly neutralizing antibodies targeting quaternary epitopes. To date, no studies have measured the levels and kinetics of serum antibodies directed to such epitopes among populations in regions where dengue is endemic. Here, we use a recombinant DENV4 (rDENV4/3-M14) displaying a major DENV3 type-specific quaternary epitope recognized by human monoclonal antibody 5J7 to measure the proportion, magnitude, and kinetics of DENV3 type-specific neutralizing antibody responses targeting this epitope. Primary DENV3 sera from 30 individuals in a dengue hospital-based study in Nicaragua were studied 3, 6, 12, and 18 months post-infection, alongside samples collected annually 1 to 4 years post-primary DENV3 infection from 10 individuals in a cohort study in Nicaragua. We found substantial individual variation in the proportion of DENV3 type-specific neutralizing antibody titers attributed to the 5J7 epitope (range, 0 to 100%), with the mean significantly increasing from 22.6% to 41.4% from 3 to 18 months. We extended the transplanted DENV3 5J7 epitope on the virion (rDENV4/3-M16), resulting in increased recognition in several individuals, helping define the footprint of the epitope. However, 37% and 13% of the subjects still showed little to no recognition of the 5J7 epitope at 3 and 18 months, respectively, indicating that one or more additional DENV3 type-specific epitopes exist. Overall, this study demonstrates how DENV-immune plasma from populations from areas of endemicity, when coupled with structurally guided recombinant viruses, can help characterize the epitope-specific neutralizing antibody response in natural DENV infections, with direct implications for design and evaluation of dengue vaccines. IMPORTANCE The four serotypes of dengue virus cause dengue, a major public health burden worldwide, yet it has been challenging to develop a vaccine that is safe and equally effective against all four serotypes. More in-depth characterization of natural human neutralizing antibody responses is needed to identify determinants of protective antibody responses to all DENV serotypes. Here, we use hospital and cohort studies in a region where dengue is endemic to assess the proportion and kinetics of the DENV3 neutralizing antibody response directed to a quaternary epitope on DENV3 recognized by strongly neutralizing human monoclonal antibody 5J7, which was transplanted into a DENV4 backbone. We show that many individuals recognized the 5J7 epitope, but to various degrees over time, suggesting that additional DENV3-specific epitopes likely exist. Thus, characterization of epitope-specific neutralizing antibody responses in natural DENV infections can help define the footprint and repertoire of antibodies directed to DENV3 type-specific epitopes, with implications for dengue vaccine development.